Isolation and Identification of Luminescent Bacteria in Deep Sea Marine Organisms from Sicilian Waters (Mediterranean Sea) - Rosario Calogero; Carmen Rizzo; Erika Arcadi; Maria Giulia Stipa; Pierpaolo Consoli; Teresa Romeo; Pietro Battaglia (Journal of Marine Science and Engineering, 2022)
Luminescent bacteria are a fascinating component of marine microbial communities, often related to the light emissions in deep sea marine organisms. They are mainly affiliated with specific phylogenetic groups, such as Photobacterium, Vibrio, and Photorhabdus, and are sometimes involved in symbiotic relationships. However, the luminescence of some marine organisms remains a poorly understood process, and it is not always certain whether their luminescence is attributable to associated luminescent bacteria. In this study, for the first time, luminescent bacteria were isolated from two deep sea organisms, namely, the cephalopod Neorossia caroli and the teleost Chlorophthalmus agassizi. The isolation was carried out on glycerol-supplemented medium, and the search for the luxAB gene was performed on all isolates as a complementary tool to the culture-dependent techniques to detect bioluminescence by molecular approach. The optimum of salinity, temperature, and pH was evaluated by physiological tests for all isolates. The production of extracellular polymeric substances was also preliminarily screened. A total of 24 luminescent isolates were obtained, with an abundance from C. agassizi specimens. All the isolates were taxonomically characterized and were related to different species of Photobacterium, with the exception of Vibrio sp. CLD11 that was from C. agassizi. The luxAB gene was detected in about the 90% of the analysed strains.

“New records of rare species in the Mediterranean Sea” (October 2021) - KONSTANTINOS TSAGARAKIS; SANDRA AGIUS DARMANIN; SARA A.A. AL MABRUK; ROCCO AURIEMMA; ERNESTO AZZURRO; NICHOLAS BADOUVAS; RIGERS BAKIU; MICHEL BARICHE; PIETRO BATTAGLIA; FEDERICO BETTI; DIEGO BORME; ROBERTO CACCIAMANI; et al. (Mediterranean Marine Science, 2021)
“New records of rare species in the Mediterranean Sea” (October 2021)

Age, Growth and Otolith Microstructure of the Spotted Lanternfish Myctophum punctatum Rafinesque 1810 - Francesco Longo; Danilo Malara; Maria Giulia Stipa; Pierpaolo Consoli; Teresa Romeo; Marilena Sanfilippo; Francesco Abbate; Franco Andaloro; Pietro Battaglia (Journal of Marine Science and Engineering, 2021)
This study investigated, for the first time, the age and growth of the spotted lanternfish Myctophum punctatum through an analysis of otolith microstructure. A total of 377 individuals were collected from the Strait of Messina (central Mediterranean Sea), ranging between 20.3 and 73.7 mm of standard length. Their length–weight relationship was estimated, and these outputs indicated an isometric growth, for all specimens and when males and females were analysed separately. The sagittal otoliths were removed from 185 fish, although the microincrement readings were considered valid for only 173 otoliths. Microincrement counts ranged from 32 to 48 (average = 37.6) in the otolith central zone, 30 to 56 (average = 44.3) in the middle zone, and 36 to 384 (average = 165.5) in the external zone. Overall, total microincrements ranged between 106 and 469. Different growth models (Gompertz, von Bertalanffy and logistic models) were considered, to understand which one fit best in describing the growth patterns in M. punctatum. The Gompertz model was then selected as the best-fitting model and its parameters for all individuals were L∞ = 74.79, k = 0.0084 and I = 139.60.